An overview of the prevalence of malocclusion in 6 to 10-year-old children in Brazil - Bittencourt, Marcos Alan Vieira; Machado, André Wilson [UNESP] (FapUNIFESP (SciELO), 2010)
Objective: To provide an overview of the malocclusions present in Brazilian children aged 6 to 10 years, and present two clinical situations often associated with these malocclusions, i.e., caries and premature loss of deciduous teeth. Methods: A sample comprised of 4,776 randomly and intentionally selected children was evaluated. Data collection was performed by clinical examination and anamnesis as part of the campaign Preventing is better than treating conducted in 18 Brazilian states and the Federal District involving orthodontists affiliated with the Brazilian Association of Orthodontics and Facial Orthopedics (ABOR). Results and Conclusions: It was noted that only 14.83% of the children had normal occlusion while 85.17% had some sort of altered occlusion, with 57.24% presenting with Class I malocclusion, 21.73%, Class II, and 6.2%, Class III. Crossbite was also found in 19.58% of the children, with 10.41% in the anterior and 9.17% in the posterior region. Deep overbite was found in 18.09% and open bite, in 15.85% of the sample. Caries and/or tooth loss were present in 52.97% of the children. Moreover, the need for preventive orthodontics was observed in 72.34% of the children, and for interceptive orthodontics, in 60.86%. It should therefore be emphasized that the presence of specialists in orthodontics-duly qualified to meet the standards established by ABOR and the World Federation of Orthodontists (WFO)-in attendance at public health clinics, can greatly benefit underprivileged Brazilian children.
Keywords: Epidemiology; Malocclusion; Prevalence